Temporal changes in cecal luminal and mucosal microbiota of broiler chickens with clinical coccidiosis (Eimeria maxima) - Philip M. Campos; Katarzyna B. Miska; Mark C. Jenkins; Monika Proszkowiec-Weglarz (PLoS ONE, 2025)
Coccidiosis is a gastrointestinal disease caused by Eimeria parasites which leads to major economic losses in the poultry industry worldwide. Eimeria infection may alter the gut microbiota, which has been associated with chicken health and performance. This study aimed to determine the effects of Eimeria maxima infection on the luminal and mucosal microbiota of the cecum (CeL and CeM) at multiple time points post-infection (days 3, 5, 7, 10, and 14). Infection decreased Shannon diversity at d 3 (P = 0.03), increased observed features (ASVs) at d 5 (P < 0.01), and increased Shannon diversity at d 10 (P = 0.04) in the CeL microbiota compared to the control. In CeM microbiota, infection increased observed features at d 5 (P = 0.03), but later decreased observed features at d 14 (P = 0.01). Relative abundance of potential butyrate-producing bacteria such as [Ruminococcus] torques group in CeL and Butyricicoccus in CeM were decreased in infected birds, and some metabolic pathways related to butyrate production were predicted to be decreased. These findings show E. maxima may affect cecal microbiota alpha diversity in a time-dependent manner and reduce abundance of bacteria potentially important to gut health.